A case of myocarditis after COVID-19 vaccination: incidental or consequential?. Issue 6 (June 2022) - Alizadeh, Leona S.; Koch, Vitali; Yel, Ibrahim; Grünewald, Leon D.; Mathies, Daniel; Martin, Simon; Vogl, Thomas J.; Rauschning, Dominic; Booz, Christian
Abstract: Vaccination represents one of the fundamentals in the fight against SARS-CoV-2. Myocarditis has been reported as a rare but possible adverse consequence of different vaccines, and its clinical presentation can range from mild symptoms to acute heart failure. We report a case of a 29-year-old man who presented with fever and retrosternal pain after receiving SARS-CoV-2 vaccine. Cardiac magnetic resonance imaging and laboratory data revealed typical findings of acute myocarditis. Abstract : Myocarditis; Vaccination; COVID-19; MRI.